Desain Sistem Informasi Manajemen Operasional Asrama Mahasiswi - Muslihuddin Muslihuddin; Nidia Rosmawanti (STMIK Banjarbaru, 2023)
A female student dormitory is a residential building intended for a group of people who are studying at a university or college. The Student Dormitory Information System is a technology solution aimed at optimizing the management and operationalization of dormitories for female students in a tertiary institution. Here describes the design of an information system that integrates various aspects of hostel management, including registration, placement, security monitoring, inventory of facilities, and communication between dormitory residents and related staff. This study presents a solution to overcome the problem of lack of information regarding the availability of rooms at the Serai Paser Dormitory for female students. The system development approach used is the System Development Life Cycle (SDLC) with a focus on web-based prototyping methods. With the research on the Serai Female Student Dormitory Information System, Paser Regency, the positive impact is to help disseminate information about the Seratai student dormitory, facilitate the hostel management process, facilitate the preparation and reporting of dormitory information, room availability, use of facilities and facilitate the process of registration and management of room availability so as to assist the process registration.Keywords: Information System Dormitory; Female students; Prototyping AbstrakAsrama mahasiswi merupakan sebuah bangunan tempat tinggal yang diperuntukkan bagi sekelompok orang yang sedang menjalani pendidikan pada sebuah universitas atau perguruan tinggi. Sistem Informasi Asrama Mahasiswi merupakan solusi teknologi bertujuan untuk mengoptimalkan manajemen dan operasionalisasi asrama bagi mahasiswi di lingkungan perguruan tinggi. Disini menjelaskan perancangan sistem informasi yang mengintegrasikan berbagai aspek pengelolaan asrama, termasuk pendaftaran, penempatan, pemantauan keamanan, inventarisasi fasilitas, dan komunikasi antara penghuni asrama serta staf terkait. Penelitian ini menyajikan solusi untuk mengatasi permasalahan kurangnya informasi mengenai ketersediaan kamar di Asrama Seratai Paser bagi mahasiswi. Pendekatan pengembangan sistem yang digunakan adalah Siklus Hidup Pengembangan Sistem (SDLC) dengan fokus pada metode prototyping berbasis web. Dengan adanya penelitian Sistem Informasi Asrama Mahasiswi Seratai Kabupaten Paser, dampak positifnya yaitu membantu penyebaran informasi mengenai asrama mahasiswi Seratai, memudahkan proses pengelolaan asrama, memudahkan pembuatan dan pelaporan informasi asrama, ketersediaan kamar, pemakaian fasilitas serta memudahkan proses registrasi dan pengelolaan ketersediaan kamar sehingga membantu proses registrasi.